Time after apple pressing and insoluble solids influence the efficiency of the UV treatment of cloudy apple juice - Usaga Barrientos, Jessie (2015)
The effects of suspended insoluble solids (SIS) concentration and particle size, and the time after apple pressing on the efficiency of UV treatment of cloudy apple juice were evaluated. Clear model solutions (formulated to resemble physicochemical characteristics of apple juice) and commercial apple juice, containing different solids concentrations, were treated using a CiderSure reactor at 14 mJ cm−2 UV dose. Particle size effect was assessed on model solutions treated at 7 mJ cm−2 UV dose. The juice flow rate through the UV machine was determined. All samples were inoculated with Escherichia coli ATCC 25922 (106–107 CFU ml−1) and UV treated at 214.5 ml s−1 fixed flow rate. Log reductions were calculated. Increasing SIS concentrations did not significantly affect the juice flow rate (P > 0.05) but adversely affected the inactivation of E. coli (P < 0.05). For solutions treated at 7 mJ cm−2, a negative linear relationship between SIS and flow rate was observed and particle size significantly affected the flow rate (P < 0.05). A negative effect of time after apple pressing on the juice flow rate was observed and this effect was apple cultivar-dependent, thus UV efficiency would be improved if time after pressing is minimized.